2021
DOI: 10.1523/eneuro.0536-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Neuron Replating, a Powerful and Versatile Approach to Study Early Aspects of Neuron Differentiation

Abstract: Neuron differentiation includes formation and outgrowth of neurites that differentiate into axons or dendrites. Directed neurite outgrowth is controlled by growth cones that protrude and retract actin-rich structures to sense environmental cues. These cues Significance statementUnraveling the molecular mechanisms that control neuron differentiation requires reporter gene expression or gene inactivation. In mouse primary hippocampal neurons, a widely used cellular system to study neuron differentiation, classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…While we here implicated CAP1 in synaptic actin regulation, we earlier showed its relevance for actin dynamics in growth cones [61,63]. We therefore conclude a general requirement of CAP1 in neuronal actin regulation both during differentiation and in differentiated neurons, similar to cofilin1 [2,14,45,55,57,62]. By PLA we found colocalization (within 40 nm) of CAP1 and cofilin1 in the dendritic compartment, and our co-immunoprecipitation experiments validated their physical interaction in the hippocampus, which required CAP1's HFD.…”
Section: Discussionsupporting
confidence: 80%
“…While we here implicated CAP1 in synaptic actin regulation, we earlier showed its relevance for actin dynamics in growth cones [61,63]. We therefore conclude a general requirement of CAP1 in neuronal actin regulation both during differentiation and in differentiated neurons, similar to cofilin1 [2,14,45,55,57,62]. By PLA we found colocalization (within 40 nm) of CAP1 and cofilin1 in the dendritic compartment, and our co-immunoprecipitation experiments validated their physical interaction in the hippocampus, which required CAP1's HFD.…”
Section: Discussionsupporting
confidence: 80%
“…By exploiting cortical neurons from gene-targeted mice, the present study aimed at identifying ABPs that act upstream of neuronal MRTF-SRF signaling. Because previous studies identified members of the actin-depolymerizing factor (ADF)/cofilin family of actin-depolymerizing proteins as essential regulators of the neuronal actin cytoskeleton relevant for brain development, synapse physiology, and behavior (18)(19)(20)(21)(22)(23)(24)(25)(26), we did not expect to find neuronal MRTF-SRF activity unchanged upon inactivation of either cofilin1 or ADF and only slightly increased upon inactivation of both ADF/cofilin proteins. Instead, SRF activity was strongly increased upon inactivation of cyclase-associated protein 1 (CAP1) but not of its homolog CAP2.…”
Section: Introductionmentioning
confidence: 90%
“…Primary cortical neurons from E18 mice of both sexes were prepared as previously described ( 26 ). In brief, cerebral cortices from the same litter were pooled together, treated with TrypLE Express (Gibco) for 6 min at 37°C, and dissociated with pipetting up and down six or seven times.…”
Section: Methodsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted February 28, 2024. ; https://doi.org/10.1101/2024.02.26.582060 doi: bioRxiv preprint previous studies let members of the actin-depolymerizing factor (ADF)/cofilin family emerge as essential regulators of the neuronal actin cytoskeleton relevant for brain development, synapse physiology and behavior (Bellenchi et al, 2007;Hotulainen et al, 2009;Rust et al, 2010;Flynn et al, 2012;Goodson et al, 2012;Wolf et al, 2015;Zimmermann et al, 2015;Sungur et al, 2018;Schneider et al, 2021a), we were surprised to find them largely dispensable for neuronal MRTF-SRF activity.…”
Section: Introductionmentioning
confidence: 97%
“…By exploiting cortical neurons from gene-targeted mice, the present study aimed at identifying ABP that act upstream of neuronal MRTF-SRF signaling. Because previous studies let members of the actin-depolymerizing factor (ADF)/cofilin family emerge as essential regulators of the neuronal actin cytoskeleton relevant for brain development, synapse physiology and behavior (Bellenchi et al, 2007; Hotulainen et al, 2009; Rust et al, 2010; Flynn et al, 2012; Goodson et al, 2012; Wolf et al, 2015; Zimmermann et al, 2015; Sungur et al, 2018; Schneider et al, 2021a), we were surprised to find them largely dispensable for neuronal MRTF-SRF activity. Instead, SRF activity was strongly increased upon inactivation of cyclase-associated protein 1 (CAP1), but not of its homolog CAP2.…”
Section: Introductionmentioning
confidence: 99%